((P=P)=(-P=-P)) v ((P=P)=/=(-P=-P))

What is the basis for reason? And mathematics?

Moderators: AMod, iMod

Post Reply
Eodnhoj7
Posts: 6220
Joined: Mon Mar 13, 2017 3:18 am

((P=P)=(-P=-P)) v ((P=P)=/=(-P=-P))

Post by Eodnhoj7 »

((P=P)=(-P=-P)) v ((P=P)=/=(-P=-P))

1. ((P=P)=(-P=-P)) necessitates under the law of identity that two opposing values are equal through the law of identity, thus negating the law of non contradiction where P cannot equal not P.

So the law of non contradiction is negated.






2. ((P=P)=/=(-P=-P)) necessitates under the law of non-contradiction that two principles equal through the law of identity are not equal, thus the law of identity is not equal to itself.

And the law of identity is negated.





3. ((P=P)=(-P=-P)) v ((P=P)=/=(-P=-P)) necessitate either the law of identity or the law of non contradiction results, thus negating either the fallacious use of the law of identity or the fallacious use of the law of non-contradiction but not both.

Either the law of identity or the law of non contradiction is negated. If the law of non contradiction is negated then the law of identity ceases to exist as P = -P. If the law of identity is negated then the law of non contradiction is negated as P = -P.
Post Reply